(untitled) (JISTECH: Journal of Information Science and Technology, 2023)
Seismic waves travelling through media are attenuated by the conversion of elastic energy into heat. Upon being attenuated, the travelling wave changes: amplitude is reduced, travelling waveform is modified due to high-frequency content absorption, and phase is delayed. In this study, the effect of attenuation on seismic data was reduced by applying inverse Q filter method. Application of inverse Q filter on seismic data, can improve the quality and resolution of data. Improving the seismic data quality and its resolution can be seen at seismic attributes (Instantaneous Amplitude) of seismic data. The results of study indicate that the seismic attributes (instantaneous amplitude) would be better if the inverse Q filter was applied.